Oor die inhoud en boodskap van die Heidelbergse Kategismus - D. Smit (Acta Theologica)
The essay argues that it is meaningful to speak about the theme, content and message of the Heidelberg Catechism, although these three should be distinguished. A first section claims that the Catechism shows more of a single argument and purpose than many other catechisms of the time, because they often consisted of a mere compilation of diverse material, without clear purpose. A second section further develops this claim by showing how the comfort of the first question and answer forms the continuing motif, providing the theme and structure of the Catechism. A third section serves as reminder of Barth’s claim that Jesus Christ is the content of this comfort and therefore of the Heidelberg Catechism. A fourth section suggests a final distinction, arguing that the message is still different from the purpose, theme and content, since it depends on specific readers in their own contexts, as the reception history has shown.